NILAI-NILAI PENDIDIKAN ISLAM DALAM NOVEL JANGAN BERCERAI BUNDA KARYA ASMA NADIA - Asmarita Asmarita; Isti Fatonah (JPMUJ, 2025)
This research is motivated by the increasing occurrence of family problems in society, largely due to the diminishing emphasis on instilling Islamic educational values within the family, which weakens the foundation or guidance in dealing with life’s challenges. The purpose of this research is to examine the values of Islamic education present in the novel Jangan Bercerai Bunda. This study is categorized as library research, with data collected through documentation techniques, interviews, and analyzed using content analysis. Based on the data, the results of this study show that there are three primary Islamic educational values in the novel Jangan Bercerai Bunda: aqidah (faith), akhlak (morality), and ibadah (worship). Aqidah includes the utterance of phrases like Alhamdulillah, Bismillah, Masha Allah, Astaghfirullah, belief in the messengers of Allah, emulating the story of Prophet Yusuf resisting temptation from Zulaikha, and faith in qada' and qadar manifested through sincerity, patience, and trust in Allah (tawakkal). The aspect of akhlak involves behavior, such as morality towards Allah, expressed in worship like prayer, ablution, and trust in Him. Akhlak towards oneself includes honesty, patience, optimism, humility, and responsibility. Akhlak towards others includes empathy, avoiding grudges, and forgiveness. The value of ibadah includes both ibadah mahdah (obligatory worship, such as daily prayers, istikharah, and ablution) and ibadah ghairu mahdah (non-obligatory worship, like prayer and seeking knowledge).If these three values are applied in family life, they will foster a harmonious, peaceful, and conflict-free household that feels closer to Allah. Moreover, such a family can serve as an inspiration to others.